Impact of exclosures on wood biomass production and fuelwood supply in northern Ethiopia - Mekuria, Wolde; Yami, M.; Haile, M.; Gebrehiwot, K.; Birhane, E. (Springer, 2019)
In the Ethiopian highlands, communal grazing lands are one of the major land uses, and are source of livelihood for the rural people. Free and uncontrolled grazing in the communal grazing lands is the dominant grazing system. The traditional uncontrolled and free grazing system has caused severe degradation of the grazing lands. As a result, communities have started to establish exclosures and support the restoration of degraded communal grazing lands. Studies have shown that exclosures are effective to restoring degraded communal grazing lands and improving ecosystem services. However, studies that investigate the changes in above ground biomass following the establishment of exclosures and compare it with fuelwood demand of the beneficiaries in our study area is lacking. Therefore, our study aimed at: (1) quantifying yearly biomass accumulation in exclosures and compare it to fuelwood demand of households that manage the exclosures; (2) assessing household energy sources and their consumption levels. To monitor changes in biomass production with over time, replicated (n = 3) 5 and 10 year-old exclosures were sampled. To investigate fuelwood sources and consumption patterns, household surveys, key informant interviews and focus group discussion were conducted. Our results demonstrated that total biomass production increased with exclosure age. In both exclosure, biomass production from Vachellia etbaica was significantly (p\0.05) greater than that from Euclea. racemosa. Average daily fuelwood consumption per person was (0.63 ± 0.2) kg day-1. This means that the total biomass (27.5 Mg year-1) obtained from 114.6 ha of exclosures covers only 9.4% of yearly fuelwood demand of the residents who manage the sampled exclosures. Nearly all respondents (95%) confirmed that they travel more than 10 km day-1 to gather fuelwood from surrounding degraded forest patches. We recommend plantings of fast growing native tree species within exclosures and around homesteads to provide a sustainable fuelwood supply and using improved stoves to address the problem of fuelwood shortage. District agricultural offices could provide seedlings of native plant species, while communities provide unpaid labour for planting and managing plantations.